Experimental study of the shadow effect on a monocrystalline silicon photovoltaic module - Bounechba Hadjer; Boussaid Abdelfettah; Benlabed Wassim Mustapha; Mouat Nidal (Serbian Journal of Electrical Engineering)
The ultimate component of photovoltaic energy conversion into electrical power is the solar cell. The best efficiency of this conversion is obtained for a group of few cells in parallel or in series, forming what is called “a solar module”. This grouping requires special precautions in order to avoid panel degradation, occurring when the amount of incident radiation received by a photovoltaic module is not the same (Shading Effect). This results in a dispersion of cell parameters, some cells become resistive and heat up (hot spots), thus producing significant power dissipation and reducing the characteristics of the PV module. In order to preserve the solar panel and lessen the shadow affect, bypass diodes are utilized. In the present research, a Matlab/Simscape model is used to plot I-V and P-V panel characteristics, under different numbers of shaded cells, with and without bypass diodes to illustrate the effects of partial, total and random shading on the PV module performance. Furthermore, our aim is to show how adding bypass diodes changes the performance of a partially shaded solar system. Experimental tests were carried out within the Frères Mentouri Constantine 1 University of Constantine / Electrical Engineering Laboratory (LEC) in order to study the effects of total, partial and non-uniform shading of mono crystalline silicon photovoltaic module (80W) with 36 cells connected in series (every 18 cells in the panel have one bypass diode). The obtained experimental data indicate that the PV module power decreases up to almost 50% in case of full shading, and up to 30% in case of application of partial shading.